Design and fabrication of foldable wet shopping cart - Nur Ain Izzati, Zainudin (2009)
This report presents about the Design and Fabrication of Foldable Wet Shopping Cart. The foldable wet shopping cart is device for users to put any groceries while shopping at market. The foldable wet shopping cart is design according to the existing market demand and to fulfill the criteria of customer needs. The design of this folding cart considers durability, easy to use, and ergonomic factor. The concept of the foldable wet shopping cart will be more innovation from the existing product special for Asians user. The selection of suitable materials for this fabrication of folding cart is a loaded material which has minimum weight and can detain heavy load. Materials are proposed for the fabrication of cart is mild steels. This Foldable Wet Shopping Cart is equipped by using all necessary items and methods for instance hollow mild steel, oval hollow steel, round bar, plate bar, elbow pipe, wheels, mosquito net, skills in manufacturing processes, metal inert gas (MIG) welding to join the parts, drilling and also mechanical fasteners. This folding cart would be entirely different from existing shopping cart.